Biological control of clubroot on cauliflower with Trichoderma and Streptomyces spp - Cheah, L-H; Veerakone, S.; Kent, G. (New Zealand Plant Protection, 2000)
The effectiveness of Trichoderma and Streptomyces spp in suppressing clubroot of brassicas which is caused by Plasmodiophora brassicae was tested on cauliflower seedlings in glasshouse and field crops The glasshouse experiment showed that of fifteen isolates of Trichoderma spp and one Streptomyces sp tested six of these reduced (P